The Limits of Community Policing : Civilian Power and Police Accountability in Black and Brown Los Angeles - Gascón, Luis Daniel (Book collections on Project MUSE., 2019)
"The Limits of Community Policing' addresses conflicts between police and communities. Luis Daniel Gascón and Aaron Roussell depart from traditional conceptions, arguing that community policing-popularized for decades as a racial panacea-is not the solution it seems to be. Tracing this policy back to its origins, they focus on the Los Angeles Police Department, which first introduced community policing after the high-profile Rodney King riots. Drawing on over sixty interviews with officers, residents, and stakeholders in South LA's "Lakeside" precinct, they show how police tactics amplified-rather than resolved-racial tensions, complicating partnership efforts, crime response and prevention, and accountability. Gascon and Roussell shine a new light on the residents of this neighborhood to address the enduring-and frequently explosive-conflicts between police and communities. At a time when these issues have taken center stage, this volume offers a critical understanding of how community policing really works."--Résumé de l'éditeur.